Admission fibrinogen levels in severe trauma patients: A comparison of elderly and younger patients. Issue 9 (September 2015) - Ohmori, Takao; Kitamura, Taisuke; Tanaka, Kimiaki; Saisaka, Yuichi; Ishihara, Junko; Onishi, Hirokazu; Nojima, Tsuyoshi; Yamamoto, Koutarou; Matusmoto, Toshiyuki; Tokioka, Takamitsu
Abstract Introduction Acute coagulopathy of trauma has been much discussed recently. However, the changes in coagulation markers after trauma in the elderly are unknown. Furthermore, the baseline fibrinogen level is high in elderly patients, and the question remains as to whether fibrinogen levels also decrease early and the degree of decrease in elderly trauma patients. The purpose of this study was to compare coagulation markers including the fibrinogen level on admission in younger and elderly severe trauma patients. Methods A cohort of severe trauma patients (Injury Severity Score (ISS) ≥16), admitted from January 2011 to June 2014, with coagulation markers including the fibrinogen level on admission available, was reviewed retrospectively. The patients were divided into a younger (16–64 years old) and an older (≥65 years old) group based upon their age at presentation. Activated partial thromboplastin time (aPTT), international normalized ratio (INR), fibrinogen, and D-dimer were compared between the younger and older groups. Results There were 251 patients who met the inclusion criteria for this analysis. The younger group included 117 patients and the older group included 134 patients. The median aPTT (26.3 vs 27.5 s, P = 0.001) and median D-dimer levels (18.8 vs 40.2 μg/dL, P = 0.006) were significantly higher in the older group. However, the fibrinogen level (205 vs 248 mg/dL, P < 0.001) was significantly higher in the older group. The regression lines of fibrinogen and age in non-massive transfusion and massive transfusion cases are given by Y = 1.03X + 185 (r = 0.24, r2 = 0.06, P < 0.001) and Y = 0.86X + 134 (r = 0.25, r2 = 0.06, P = 0.09) respectively, and the fibrinogen levels tended to increase with older age in severe trauma patients. Conclusions The fibrinogen level did not show a low value as it can in younger patients in elderly patients. Therefore, the fibrinogen level is difficult to use as an early indicator of acute blood loss with haemorrhage in elderly severe trauma patients, as it can be used in younger patients. Thus, it is necessary to keep in mind that the fibrinogen level increases by approximately 1 mg/dL when the age increases by 1 year and to carefully observe the fibrinogen level even if the admission level is not low.